THE INFLUENCE OF ISLAM ON SCIENCE AND EDUCATION IN THE MIDDLE AGES - Шамсутдинова-Лебедюк, Тетяна; Лебедюк, Єлизавета; Шамсутдинов, Баходир (SWorldJournal, 2025)
The article is devoted to the study of the influence of Islam on the development of science and education in the Middle Ages, in particular during the Islamic Golden Age (8th–14th centuries). The work analyzes the establishment of the first Islamic educat